Analysis of Employee Performance at the South Langowan District Office, Minahasa Regency - Wowiling, Wilson W.; Mokat, Jetty E. H.; Kairupan, Sisca B. (Technium Social Sciences Journal, 2025)
This study aims to analyze the performance of employees in South Langowan District Office, Minahasa Regency by focusing on internal factors that affect performance, namely attitude and behavior, motivation, and work discipline. Employee performance is a crucial element in public service, and understanding the factors that influence it is very important to improve organizational effectiveness. This research uses qualitative research methods. Data sources were obtained from primary data, namely interviews and secondary data, namely supporting data in the field such as literature and documents. In conducting data analysis, researchers refer to several stages consisting of several stages, including data reduction, data presentation and conclusion drawing. The results showed that the Performance of Employees of the South Langowan District Office of Minahasa Regency in terms of Indicators of Employee Attitude and Behavior was still less open if criticized. Judging from the Motivation indicator, it still needs to be strengthened through coaching for the development of Human Resources. Judging from the indicator of work discipline, it is still necessary to get guidance because staffing rules are still violated by employees. In conclusion, Employee Performance at the South Langowan District office is not optimal. The reality is still not in line with expectations.